The Interaction of Electromagnetic Waves from Sheets of Spherical Nano-elements Meshed on Concentric Spherical Shells - Sengor, T. (ELECTROMAGNETICS ACAD, 2012)
Possibilities creating nano-structures providing unnatural electromagnetic characteristics are given. Co-rings in nano-metric dimensions lying on different azimuth and/or equatorial planes are defined as nano-element providing such possibilities. These nano-elements are meshed on concentric spherical shells. The interaction of electromagnetic wave with both of nano element and meshed spherical surface are studied. For an example, the necessary configurations for both of the electromagnetically effective cloaking and the optically effective cloaking (invisibility) are given for this purpose.
Keywords: Engineering; Physics